PENGARUH PADAT KARYA TUNAI TERHADAP TINGKAT KEMISKINAN DI PEDESAAN PROV. JAWA BARAT DAN RIAU - Deni Herdiyana (Jurnal Ekonomi dan Industri, 2019)
Cash for Work in the Village (CfWV) is one of the Village Fund revitalization programs conducted to empower rural communities, especially the poor and marginal, who are productive by prioritizing the use of resources, labor, and local technology to provide additional income, reduce poverty, and improve people's welfare. This study aims to analyze the implementation of CfWV policies in West Java and Riau Provinces. The method used is by conducting observations and interviews with stakeholders in the village which are categorized as Disadvantaged Villages or Very Disadvantaged Villages with a high number of poor people. In addition, a policy implementation approach which formulated by George C. Edward III was used to describe policy implementation variables, such as communication, resources, attitudes / dispositions, and bureaucratic structures. The findings of this study include: a tendency to decrease the spirit of mutual cooperation, the provision of a 30% minimum Working Day (HOK) Day is not fully suitable, and this program has not been able to permanently improve community welfare due to the temporary nature of its activities. Although this program is worth continuing, there needs to be some improvements, including the selection of activities that are more flexible in accordance with village needs and the expansion of community empowerment activities.